Contribuição científica brasileira sobre Helicobacter pylori: uma análise bibliométrica no século XXI - Comin, Janaina (My University, 2025)
Introduction: Helicobacter pylori is one of the most prevalent infectious agents worldwide, strongly associated with chronic gastritis, peptic ulcers, and gastric neoplasms. However, the Brazilian scientific contribution in this field had not yet been analyzed from a bibliometric perspective. Objective: To map and analyze Brazilian scientific production on H. pylori between 2001 and 2024, identifying publication trends, institutional participation, collaboration networks, and main thematic focuses. Methods: A descriptive and quantitative bibliometric analysis was performed based on the PubMed database. Publications with at least one author affiliated with a Brazilian institution were included. Bibliographic data were analyzed in Microsoft Excel and visualized with VOSviewer software (version 1.6.16), allowing the mapping of co-authorship networks, institutional collaboration, and co- occurrence of terms. Results: 667 publications were identified, with progressive growth until 2019 and stabilization in subsequent years. Most studies were observational or review articles, concentrated in public universities in the Southeast and South regions. Antimicrobial resistance, eradication therapies, and virulence mechanisms were the main topics addressed. There were relevant international collaborations, especially with Portugal, Italy, and Japan, and a predominance of female authorship in leading positions. Conclusion: Brazilian research on H. pylori reveals thematic diversification, institutional strengthening, and increasing international integration, although regional inequalities persist. The expansion of multicenter networks, the integration of bibliometric and epidemiological data, and the investigation of emerging topics, such as vaccines and nanomaterial-based therapies, can broaden Brazil's contribution to global research on H. pylori. [resumo fornecido pelo autor]
Introdução: Helicobacter pylori é um dos agentes infecciosos mais prevalentes no mundo, fortemente associado à gastrite crônica, úlcera péptica e neoplasias gástricas. No entanto, a contribuição científica brasileira nesse campo ainda não havia sido analisada sob a perspectiva bibliométrica. Objetivo: Mapear e analisar a produção científica brasileira sobre H. pylori entre 2001 e 2024, identificando tendências de publicação, participação institucional, redes de colaboração e principais focos temáticos. Métodos: Foi realizada uma análise bibliométrica descritiva e quantitativa com base na base de dados PubMed. Foram incluídas publicações com pelo menos um autor vinculado a instituição brasileira. Os dados bibliográficos foram analisados no Microsoft Excel e visualizados com o software VOSviewer (versão 1.6.16), permitindo o mapeamento de redes de coautoria, colaboração institucional e coocorrência de termos. Resultados: Foram identificadas 667 publicações, com crescimento progressivo até 2019 e estabilização nos anos seguintes. A maioria dos estudos foi observacional ou de revisão, concentrada em universidades públicas das regiões Sudeste e Sul. Resistência antimicrobiana, terapias de erradicação e mecanismos de virulência foram os principais temas abordados. Houve colaborações internacionais relevantes, especialmente com Portugal, Itália e Japão, e predomínio de autoria feminina nas posições principais. Conclusão: A pesquisa brasileira sobre H. pylori revela diversificação temática, fortalecimento institucional e crescente integração internacional, embora persistam desigualdades regionais. A expansão de redes multicêntricas, a integração de dados bibliométricos e epidemiológicos e a investigação de temas emergentes, como vacinas e terapias baseadas em nanomateriais, podem ampliar a contribuição do Brasil para a pesquisa global sobre H. pylori. [resumo fornecido pelo autor]
Keywords: Infecções por Helicobacter pylori; Produção científica; Bibliometria - Análise